Emergency awareness for animals: a Korean experience. Issue 1 (1st January 2019) - Cho, Gook Hyung; Ha, Kyoo-Man
ABSTRACT: Despite the significant number of animals or the high frequency of animal-related emergencies, Korea remains in the middle of emergency unawareness when it comes to handling the animals. The goal of this article is to examine how emergency unawareness for animals in Korea can be improved for the ultimate goal of emergency management. This article used qualitative content analysis as the major methodology. A careful comparison between emergency unawareness and emergency awareness for animals was done by cross-examining various animals and major stakeholders. One major finding is that Korea needs to recognize and strengthen the need for emergency awareness toward animals that are affected by emergencies (e.g. rescuing of pets during natural disasters like typhoons with flooding) as well as toward animals that caused and at the same time that are affected by emergencies (e.g. bird flu). Neighbouring nations may learn the significance of comprehensive emergency management for their animal emergency issues. This research is valuable because it used a more comprehensive perspective on animal issues compared with similar studies.